1993
DOI: 10.1093/hmg/2.10.1535
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of juvenile Huntington disease: the major influence on (CAG)n repeat length is the sex of the affected parent

Abstract: Juvenile Huntington disease (HD), characterised by onset of symptoms before the age of 20 with rigidity and intellectual decline, is associated with a predominance of affected fathers. In order to investigate the molecular basis for the observed parental effect, we have analysed the CAG trinucleotide repeat within the HD gene in 42 juvenile onset cases from 34 families. A highly significant correlation was found between the repeat length and age of onset (r = -0.86, p < 10(-7) and it was determined that the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
111
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(122 citation statements)
references
References 1 publication
10
111
1
Order By: Relevance
“…In contrast, maternal age did not influence anticipation (36). It has been shown subsequently that anticipation is closely correlated with an expansion o f the CAG repeat, and in cases o f very large expansions results in juvenile onset (16). Taken together, these data would appear to suggest that older fathers are more likely to transmit further expanded CAG repeats, with anticipation in the affected offspring.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In contrast, maternal age did not influence anticipation (36). It has been shown subsequently that anticipation is closely correlated with an expansion o f the CAG repeat, and in cases o f very large expansions results in juvenile onset (16). Taken together, these data would appear to suggest that older fathers are more likely to transmit further expanded CAG repeats, with anticipation in the affected offspring.…”
Section: Discussionmentioning
confidence: 79%
“…Age of onset is inversely correlated with the CAG repeat length, such that a longer repeat in a patient is associated with a younger age of onset (8)(9)(10)(11)(12)(13)(14)(15). Analysis of 42 juvenile onset probands revealed that the anticipation observed in these families is closely correlated with an intergenerational expansion of the repeat, from the adult onset parent to the juvenile onset child (16). The largest expansions occurred exclusively via male transmission, providing an explanation for the previously recognised predominance of affected fathers of patients with juvenile onset disease (1,2,17).…”
Section: Huntington Disease (Hd) Is a Neurodegenerative Disorder Inhementioning
confidence: 99%
See 1 more Smart Citation
“…Earlier onset in successive generations within a pedigree or anticipation in HD has predominantly been reported to originate from paternal transmission through unknown mechanism(s) [Telenius et al, 1993;Trottier et al, 1994]. Juvenileonset HD before the age of 20 years occurs in about 5% of HD cases [Potter et al, 2004], and is associated with very large ( 60) CAG repeat expansions [Nance and Myers, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Cannella et al [2004] report a mean intergenerational expansion of þ7.3 repeats with paternal transmission and þ0.7 repeats with maternal transmission. In addition to parental sex, the size of parental CAG repeats influences the extent of intergenerational expansion [Telenius et al, 1993Kremer et al, 1995;Leeflang et al, 1995]. The largest reported intergenerational expansion is þ160 repeats wherein a father with 54 repeats had a child with 214 repeats [Seneca et al, 2004].…”
Section: Introductionmentioning
confidence: 99%